Infection-mediated priming of phagocytes protects against lethal secondary Aspergillus fumigatus challenge - Savers, Amélie; Rasid, Orhan; Parlato, Marianna; Brock, Matthias; Jouvion, Gregory; Ryffel, Bernhard; Cavaillon, Jean-Marc; Eberl, Gerard; Ibrahim-Granet, Oumaïma (Public Library of Science, 2016)
Phagocytes restrict the germination of Aspergillus fumigatus conidia and prevent the establishment of invasive pulmonary aspergillosis in immunecompetent mice. Here we report that immunecompetent mice recovering from a primary A. fumigatus challenge are protected against a secondary lethal challenge. Using RAGγc knock-out mice we show that this protection is independent of T, B and NK cells. In protected mice, lung phagocytes are recruited more rapidly and are more efficient in conidial phagocytosis and killing. Protection was also associated with an enhanced expression of CXCR2 and Dectin-1 on bone marrow phagocytes. We also show that protective lung cytokine and chemokine responses are induced more rapidly and with enhanced dynamics in protected mice. Our findings support the hypothesis that following a first encounter with a non-lethal dose of A. fumigatus conidia, the innate immune system is primed and can mediate protection against a secondary lethal infection.